(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2015)
The aim of this paper is to understand hermeneutics, especially legal hermeneutics, through the theory of language. This approach will focus on language, not as a way of translating and expressing thought, that is, our ideas, but the relationship between language and the world, as a logical structure, a representation of the world that forms realities, present in our century, with language being the motto for the construction of the meaning of the norm made from its interpreter. The linguistic turn has altered meanings and philosophical knowledge and, from there, the view of reality, providing scientific, theoretical and methodological concepts, breaking with the theories that had existed until then, including philosophical ones. This language is not limited to the text, but qualifies the nature and strength of the propositions, which for the Law develops a new way of thinking. Reflection that will be approached not only in a philosophical context (of ideas), but as necessary for understanding facts, a legal philosophical hermeneutics that has allowed thinking to evolve, including through logic.